Damage Boundary Study of Crystal Oscillators under Shock Environment. (6th August 2020) - Zhao, Changjian; Zhang, Zijun; Xu, Zijian; Li, Bingwei; Yu, Muchun; Niu, Zhiling
Abstract : The crystal oscillator is a widely used electronic component in a circuit, whose accuracy is strongly affected by the external mechanical environment. To depict the failure mechanism of the crystal oscillator, the damage boundary of this component under the shock environment is studied experimentally in this paper. Through subjecting "step-up" loads on different groups of crystal oscillators, two failure modes (frequency jumping and structural fracture) are monitored and validated. Experimental results prove that "frequency jumping" failure mode is governed by the value of the acceleration shock response spectrum (ASRS) in a certain frequency range, while the failure mode "structural fracture" is governed by the peak value of the ASRS. Through analyzing the shock response spectrum, damage boundaries are given for these two failure modes, which can provide a reference for component design and failure assessment.